Rethinking Communication in the Immune System: The Quorum Sensing Concept. Issue 2 (February 2019) - Antonioli, Luca; Blandizzi, Corrado; Pacher, Pál; Guilliams, Martin; Haskó, György
Abstract : Quorum sensing was first described as the communication process bacteria employ to coordinate changes in gene expression and therefore, their collective behavior in response to population density. Emerging new evidence suggests that quorum sensing can also contribute to the regulation of immune cell responses. Quorum sensing might be achieved by the ability of immune cells to perceive the density of their own populations or those of other cells in their environment; responses to alterations in cell density might then be coordinated via changes in gene expression and protein signaling. Quorum sensing mechanisms can regulate T and B cell as well as macrophage function. We posit that perturbations in quorum sensing may undermine the balance between diverse immune cell populations and predispose the host to immune abnormalities. Highlights: Immune homeostasis relies on the ability of various immune cell populations to perceive and respond to changes in their densities and thus quorum sensing is an emerging mechanism by which homeostasis can be attained. Autoinducers are signaling molecules reporting cell density. One major autoinducer for CD4 + T cells is IL-2. IgG is a major autoinducer for B cells. Autoinducers for macrophages include TNF-α and nitric oxide. Disruption of immune quorum sensing may trigger dysregulation in the size of various immune cell pools (e.g., TEff and TReg cells) and may potentially predispose to the development of immune-related disorders. Impaired access or response to inducers may cause quorum sensing abnormalities, potentially leading to the onset of pathophysiological conditions.